Morphological and odorant-binding protein 1 gene intron 1 sequence variations in Anopheles stephensi from Jaff na city in northern Sri Lanka - Surendran, S.N.; Laxshi, K.; Jayadas, T.T.P.; Kokila, S.; Tharsan, A.; Nimasha, L.; Eswaramohan, T.; Raveendran, S.; Singh, O.P.; Ramasamy, R. (Royal Entomological Society, 2022)
Three Anopheles stephensi biotypes have historically been differentiated through variations in the mode numbers of egg ridges and adult spiracular indices. Anopheles stephensi odorant-binding protein 1 gene (AsteObp1) sequences in Iran and Afghanistan have been recently interpreted to suggest that the three biotypes are sibling species. AsteObp1 intron 1 sequences, mode numbers of egg ridges and spiracular indices of An. stephensi in Jaffna city in Sri Lanka were therefore investigated in field-collected mosquitoes and short-term laboratory colonies established from them. AsteObp1 intron 1 sequences revealed the region to be polymorphic with four unique sequences, ASJF1-4, present in both short-term laboratory colonies and field-collected An. stephensi. The spiracular index did not relate to the mode number of egg ridges in Jaffna An. stephensi. The results suggested that numbers of egg ridges, spiracular indices and AsteObp1 intron 1 sequences were not useful for differentiating An. stephensi biotypes in Jaffna. It is proposed that the observed differences between An. stephensi mosquitoes in Jaffna now result from normal population variance in the context of rapidly changing bionomics in India and northern Sri Lanka.
Keywords: Anopheles stephensi; Jaffna city; Sri Lanka; Bionomics; Biotypes; Haplotypes; Malaria vectors; Morphological variations in mosquitoes; Mosquito range expansion; Odorant-binding protein 1 gene intron 1